5+6(-1)=

Simple and best practice solution for 5+6(-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+6(-1)= equation:


Simplifying
5 + 6(-1) = 0

Multiply 6 * -1
5 + -6 = 0

Combine like terms: 5 + -6 = -1
-1 = 0

Solving
-1 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 2h^2-7h-1= | | 15x-6.3=0 | | g^2+3g= | | 4t^2+8t= | | -7(x-1)=-4(x+7) | | -2x+7=9x+3 | | 5+6z= | | x/5=17 | | .25(y-b)=m | | 3t+5=-15 | | 5-2x=3+3x-4x | | 8x+10-(2x+5)=-55 | | -2(m-60)=-m | | 5m=3m+6 | | 9x=2x^2-18 | | 8x-12=15x+10 | | 6x+12=-6 | | 4+p^2+12p=0 | | 2(x-3)=x+9 | | X^2+7x-38=0 | | x^2+50x+336=0 | | 4x+12=-2(x-3) | | -3(2x-1)=4-3x | | x^2-8x-1008=0 | | s-31=20.6 | | 6x+2=8x-2 | | x^2-4x-320=0 | | 7.2+c=19 | | 25(y+1)-x^2(y+1)= | | -2x-1=0 | | x^2+43x+432=0 | | x+0.08x=4.32 |

Equations solver categories